The development of implementation of learner-centered assessment in pedagogical requalification studies - Bakutytė, Rima; Ušeckienė, Lidija; Illiško, Dzintra (Social Welfare: Interdisciplinary Approach, 2016)
The article presents the results of two empirical researches conducted in 2010 and 2015 with the graduates of pedagogical requalification studies. Referring to the analysis of the data of scientific sources and factor analysis the approaches of student-centered assessment have been emphasized, the results of both researches have been presented and referring to them the dimensions of student-centered assessment are highlighted. It has been stated that in the university under investigation, according to the graduates, student-centered assessment is becoming more and more predominant. Moreover, having performed a correlative analysis it has been shown that the respondents’ age and working experience did not have significant influence on their opinion about student-centered assessment
Keywords: learner-centered assessment; assessment for learning; university students